Development and evaluation of emulsifying systems of the material grease from Brazilian flora - Douglas Dourado; Camilla Barreto; Rafaela S. Fernandes; Ian M. R. Blanco; Danilo Oliveira; Neila Pereira; Mateus F. Leite (GarVal Editorial Ltda., 2015)
Context: Oils and butter of seed from Brazilian biodiversity are extending the range of innovative products for cosmetics development. They have a fat potential similar to skin composition, leading to the improved performance of these product. Aims: Improve the emulsions spreadability through prior screening of grease composition and studying the viscosity, and the emulsions accelerated stability. Methods: Emulsions were formulated using oils from semiarid plants from Bahia: Syagrus coronate, Pachira retusa, and Pachira aquatica, so as to compare them with oils already standard in the production of cosmetics. Spreadability and stability tests were made comparing the results. The same criteria were used with Amazon seed butter: Virola surinamensis, Butyrospermum parkii, Astrocaryum murumuru, Theobroma cacao and Theobroma grandiflorum. For the emulsions screening and performance, a system was developed for oil/ butter, following tests of accelerated stability, viscosity, and spreadability. Results: The combined system of spreadability was optimized using screening. Emollients containing oleic and palmitic acids, and light chain fatty acids obtained good spreadability. The oil emulsion containing Pachira retusa and Virola surinamensis butter had a higher viscosity. Conclusions: With high content of fatty acids such as oleic, palmitic or the light chain fatty acids obtain an appropriated appearance, texture, and spreadability for cosmetic use. Thus, oils with a low fatty acid content may be combined with butter that have a high fatty acid content and vice-versa. Analyzing and strategically combining grease composition, one can optimize the performance of cosmetic formulations.